Charge effect of water-soluble porphyrin derivatives as a prototype to fight infections caused by Acinetobacter baumannii by aPDT approaches. Issue 6 (3rd July 2022) - da Silva Canielles Caprara, Carolina; da Silva Freitas, Livia; Iglesias, Bernardo Almeida; Ferreira, Lara Beatriz; Ramos, Daniela Fernandes
Abstract: In the last decade, Acinetobacter baumannii has emerged as a pathogen associated with infections in intensive care units worldwide, especially due to its ability to resist an extensive list of antibiotics. In this context, porphyrins have emerged as an important strategy in photodynamic therapy, since they are a group of tetrapyrrolic compounds with important photochemical and photobiological activities. In this study, the antimicrobial photodynamic activity of meso -tetra(4- N-methyl -pyridyl)porphyrin (H2 TMePyP + ) and meso -tetra(4-sulfonatophenyl)porphyrin (H2 TPPS ‒ ) was evaluated against A. baumannii by minimum inhibitory concentration (MIC), anti-biofilm activity, and the interaction with antibiotics after exposure to white-light LED irradiation. The cationic derivative H2 TMePyP + was more potent (MIC = 0.61 µM) than H2 TPPS ‒, with anti-biofilm activity and increased the antimicrobial activity of ciprofloxacin and amikacin. Given these findings, the tetra-cationic porphyrins can be assumed as prototypes to optimize and develop new agents by promoting oxidative stress and inducing free radical production.